FAKTOR â FAKTOR YANG MEMPENGARUHI MANAJEMEN PAJAK DENGAN INDIKATOR TARIF PAJAK EFEKTIF PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Nurul Amsyah, 13.05.52.0071; Kartika, Andi (Students Journal of Accounting and Banking, 2018)
This study examines the effect of firm size, capital structure (leverage),profitabilty, fixed asset intensity, inventory intensity, tax incentive to tax management, and independency commisarist using effective tax rates as a indicator. This research was conducted in Indonesian Stock Exchange by manufacturing company. The sample of this study were 230 listed in Indonesian Stock exchange for years 2013-2015. Analysis tool used multiple linear regression with t test, F test, and test the coefficient of determination. The result show that there are positive effect of probability and negative effect of fixed asset intensity. Another result show that there are no signifikant effect of firm size on tax managemen, Capital structure (leverage), Inventory intensity tax incentive to tax management , and independency commisarist.Keyword: Effective tax rate, size, leverage, probability, tax management